Ferrimagnetism of dilute Ising antiferromagnets - Timonin, P.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
It is shown that nearest-neighbor antiferromagnetic interactions of identical Ising spins on imbalancedbipartite lattice and imbalanced bipartite hierarchical fractal result in ferrimagnetic order instead of antiferromagnetic one. On some crystal lattices dilute Ising antiferromagnets may also become ferrimagnets due tothe imbalanced nature of the magnetic percolation cluster when it coexists with the percolation cluster ofvacancies. As evidenced by the existing experiments on FepZn1–pF2, such ferrimagnetism is inherent property ofbcc lattice so thermodynamics of these compounds at low p can be similar to that of antiferromagnet on imbalanced hierarchical fractal.